Query translation for multilingual content with semantic technique - Norita Md Norwawi; Sundresan a/l Perumal; Emran Huda; Waka Jeng (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cross-lingual information retrieval (CLIR) allows user query in a different language from the language of target resources. Thus, translation is the key element in the query processing. There are three translation approaches: query, document, or hybrid query-document. However, query translation is very challenging due to the polysemy problem. Different linguistic nature of the languages will lead to ambiguity of meaning subsequently user’s true intention could be misinterpreted. This paper presents a semantic technique on query translation for a multilingual knowledge repository to improve the query processing. Offline translated documents or parallel corpora in English, Arabic, and Malay language including Jawi text was used as the data. Set of keywords were constructed preidentified by expert related to prophetic food. These keywords were annotated with the relevant Quranic verses, Hadith texts, Manuscript text images and scientific article determined by expert. The synonym and context-based translation was annotated together with the specific keyword. A query will do a three-way pattern match based on the keyword indexing list that link to the relevant documents. A one-stop knowledge repository on prophetic food was developed as a proof of concept using sources are from al-Quran, Hadith, classical manuscript, and scientific articles verified by experts to ensure the content authenticity and integrity.